The ever-changing past : why all history is revisionist history - Banner, James M., Jr., 1935- (Yale University Press, 2021)
"History is not, and has never been, inert, certain, merely factual, and beyond reinterpretation. Taking readers from Thucydides to the origin of the French Revolution to the Civil War and beyond, James M. Banner, Jr. explores what historians do and why they do it. Banner shows why historical knowledge is unlikely ever to be unchanging, why history as a branch of knowledge is always a search for meaning and a constant source of argument, and why history is so essential to individuals' awareness of their location in the world and to every group and nation's sense of identity and destiny. He explains why all historians are revisionists while they seek to more fully understand the past, and how they always bring their distinct minds, dispositions, perspectives, and purposes to bear on the subjects they study."--